Comparing "Ajr” (اجر) and “Thawab” (ثواب) and their Meanings in the Holy Quran - Shaker Amery; Mohammad Musawi (دراسات في اللغة العربيّة وآدابها)
Synonymy is a universal property of language ​​and Arabic is no exception. Our argument in this article concerns the usage and meanings the two words, "ajr and thawab" in the Holy Quran.  We explore the different semantic and grammatical dimensions and characteristics of these two words in order to specify their different meanings.  Phonological and semantic examples are provided to evidence how beauty of voice and meanings can impact emotions. Our discussion of the two words is based on various interpretations and many linguistic and literary books. We conclude that the two words "ajr” and “thawab" cannot be not synonymous terms of meaning. In fact, they refer to two different dimensions: a worldly dimension and an otherworldly dimension.